2001
DOI: 10.1248/cpb.49.1448
|View full text |Cite
|
Sign up to set email alerts
|

Release from or through a Wax Matrix System. I. Basic Release Properties of the Wax Matrix System.

Abstract: To control drug release is a topic of much interest. Matrix systems were often used as one method to control drug release. Higuchi mathematically showed the drug release properties of matrix systems, 1) and numerous investigations have been carried out since then. Based on the component, matrix systems can be roughly classified into two types, i.e., polymer and wax matrix systems. Drug release from a polymer matrix is likely to be accompanied by dissolution and/or swelling of matrix layer, and the shape and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 4 publications
3
27
0
Order By: Relevance
“…[1][2][3][4][5] It was confirmed in previous papers that ethylcellulose (EC) matrix granules and EC layered granules showed similar release properties. 1) There are many methods for the preparation of layered granules.…”
supporting
confidence: 54%
“…[1][2][3][4][5] It was confirmed in previous papers that ethylcellulose (EC) matrix granules and EC layered granules showed similar release properties. 1) There are many methods for the preparation of layered granules.…”
supporting
confidence: 54%
“…1,3) These were isoniazid JP (INZ, Yukigousei Yakuhin Kogyo Co.) and hydrogenated caster oil (HCO, Kawaken Fine Chemical Co.). The mean diameter of INZ and HCO are 10.6 and 10.3 mm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In the previous paper, 1) release property of wax matrix tablet prepared from a physical mixture was examined, and it was suggested that the structure of matrix was uniform threedimensionally.…”
mentioning
confidence: 99%
“…2,3) The release properties of the matrix system were mathematically assessed by Higuchi,4) and matrix systems have often been used as a method of controlled drug release; however, it was considered that the mathematical analysis of the release process was insufficient, because the equation can not explain the entire release process. 1,5,6) In previous papers, the release process was divided into two stages to understand the entire release process and these were analyzed using a combination of the square-root time law and cube-root law equations.…”
mentioning
confidence: 99%